Effectiveness of a pilot church-based intervention to improve breastfeeding knowledge and intention of young women in Nigeria - Olatunji, Imosi Oyesola; Leshi, Oluwatosin (World Nutrition, 2025)
BackgroundBreastfeeding remains suboptimum despite its known benefits for child health, growth, and development. Prospective parents, including young adults, play a vital role in shaping breastfeeding practices, yet a significant proportion have poor breastfeeding knowledge and intentions.ObjectiveThis pilot quasi-experimental study aimed at assessing the effectiveness of breastfeeding education in improving breastfeeding knowledge and intention of young women through church-based intervention.MethodsWomen 19-24 years of age were assigned to intervention (n=9) and comparison (n=12) groups. Intervention participants received a two-day participatory breastfeeding education with emphasis on biblical perspectives on breastfeeding, while the comparison participants were engaged in a board game unrelated to breastfeeding. Breastfeeding knowledge and breastfeeding intentions were assessed pre and post-intervention. Data were analyzed with descriptive and inferential statistics.ResultsThe results show that breastfeeding knowledge increased from 33% to 100% in the intervention group, while there was a marginal increment (from 33 to 42%) in the proportion of participants with adequate breastfeeding knowledge was observed in the comparison group. Improvement was also observed in the proportion with breastfeeding intentions in the intervention group from 44% to 100%, with a small increase from 33% to 42% in the comparison group.ConclusionsThese data suggest that targeted faith-based nutrition education could be effective in improving breastfeeding knowledge and intentions of young women. It serves as a basis for further research using a randomized controlled design with an expanded sample size and longer intervention period.